Hosting the 16th AHILA Conference in Ibadan, Nigeria: organization, achievements, challenges and lessons learnt (Journal of EAHIL, 2020)
Attending a scientific conference offers researchers several potential benefits including opportunity to present and receive constructive feedback from professional colleagues. Organizing such conference is also beneficial to the hosts who can acquire skills for coordination, communication and networking. However, the process is fraught with many challenges. One hundred and nine professionals attended the 16th AHILA conference from 22 countries in Africa, Europe and United States of America. The conference agenda was balanced, integrating skills acquisition, information for career development, sources of evidence-based free e-resources, including databases, and e-books for libraries covering health-related topics. This article describes achievement, challenges and lessons learnt in hosting the conference and could serve as a guide for health information professionals planning a similar conference in the future.